Predictors of choice of initial antifungal treatment in intraabdominal candidiasis. (August 2016) - ; Ansaldi, F.; Scarparo, C.; Diaz-Martin, A.; Palacios-Garcia, I.; Rosin, C.; Almirante, B.; Baldin, G.; Vena, A.; Bouza, E.; de Egea, V.; Tascini, C.; et al.
Abstract: Intraabdominal candidiasis (IAC) is the second most frequent form of invasive candidiasis, and is associated with high mortality rates. This study aims to identify current practices in initial antifungal treatment (IAT) in a real-world scenario and to define the predictors of the choice of echinocandins or azoles in IAC episodes. Secondary analysis was performed of a multinational retrospective cohort at 13 teaching hospitals in four countries (Italy, Greece, Spain and Brazil), over a 3-year period (2011–2013). IAC was identified in 481 patients, 323 of whom received antifungal therapy (classified as the treatment group). After excluding 13 patients given amphotericin B, the treatment group was further divided into the echinocandin group (209 patients; 64.7%) and the azole group (101 patients; 32.3%). Median APACHE II scores were significantly higher in the echinocandin group (p 0.013), but IAT did not differ significantly with regard to the Candida species involved. Logistic multivariate stepwise regression analysis, adjusted for centre effect, identified septic shock (adjusted OR (aOR) 1.54), APACHE II >15 (aOR 1.16) and presence in surgical ward at diagnosis (aOR 1.16) as the top three independent variables associated with an empirical echinocandin regimen. No differences in 30-day mortality were observed between groups. Echinocandin regimen was the first choice for IAT in patients with IAC. No statistical differences in mortality were observed between regimens, but echinocandins were administered to patients with more severe disease. Some disagreements were identified between current clinical guidelines and prescription of antifungals for IAC at the bedside, so further educational measures are required to optimize therapies.